2019
DOI: 10.1089/jwh.2017.6892
|View full text |Cite
|
Sign up to set email alerts
|

Body Weight Status and Sleep Disturbances During Pregnancy: Does Adherence to Gestational Weight Gain Guidelines Matter?

Abstract: High prepregnancy BMI together with sociodemographic correlates appear as the most critical for sleep disturbances across pregnancy. GWG is of marginal importance, especially regarding snoring. These findings confirm the importance of considering the initial body weight status of women in tailoring sleep hygiene advises irrespective of the recommendations for weight gain during pregnancy. The results also underscore the need to providing as early as possible during a pregnancy, supportive tools to ethnic minor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 30 publications
2
17
2
Order By: Relevance
“…Also, since there was a limited number of studies that examined the sleep-psychological health associations in single pregnant women, studies should target single pregnant women in order to understand how single motherhood impacts sleep and psychological health. In contrast to the hypothesis and past researchers' conclusions, 53,77 the sleep duration-depression and sleep durationanxiety/stress associations were stronger in normal weight women compared to women with overweight/obesity. Although it is wellknown that pregnant women with overweight/obesity have poorer sleep quality, shorter sleep duration, and higher risk for negative psychological health than normal weight women, these findings suggest that when normal weight women had poorer sleep quality and shorter sleep duration, there was also an increase in depression and anxiety/stress.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…Also, since there was a limited number of studies that examined the sleep-psychological health associations in single pregnant women, studies should target single pregnant women in order to understand how single motherhood impacts sleep and psychological health. In contrast to the hypothesis and past researchers' conclusions, 53,77 the sleep duration-depression and sleep durationanxiety/stress associations were stronger in normal weight women compared to women with overweight/obesity. Although it is wellknown that pregnant women with overweight/obesity have poorer sleep quality, shorter sleep duration, and higher risk for negative psychological health than normal weight women, these findings suggest that when normal weight women had poorer sleep quality and shorter sleep duration, there was also an increase in depression and anxiety/stress.…”
Section: Discussioncontrasting
confidence: 96%
“…It is hypothesized that: (1) a medium association will be observed between sleep and psychological outcomes, and (2) sociodemographic characteristics (gestational age/trimester, parity, marital status, socioeconomic status), BMI, and meeting sleep recommendations will moderate the strength of association between sleep and psychological outcomes. 14,43,[51][52][53][54][55]…”
Section: Introductionmentioning
confidence: 99%
“…Despite data suggesting sleep disturbances among pregnant patients, the influence of socioeconomic status during last months of pregnancy is not clearly understood [21, 23-25]. This mini review focuses on presenting factors contributing to poor sleep quality among pregnant patients with lower income and socioeconomic statuses, especially during their third trimesters.…”
Section: Introductionmentioning
confidence: 99%
“…However, that study consisted of 176 women only and the non-signi cant result could be due to type II error. Guinhouya et al's cohort study demonstrated best sleep quality in 2nd trimester and no signi cant difference in sleep duration throughout 3 trimesters 21 . Our study which studied comprehensively, overall sleep quality, sleep duration, sleep e ciency and sleep latency, showed that sleep disturbances are most severe in the last antenatal visit, consistent with most previous studies.…”
Section: Discussionmentioning
confidence: 92%
“…As obesity is increasingly prevalent globally and associated with sleep disorders such as sleep apnea and cause sleep disturbances in both non-pregnant and pregnant population 20 , it is interesting to explore sleep quality in women in different body mass index (BMI) groups. One large cohort study involving 2366 pregnant women by Guinhouya BC et al showed overall sleep quality was worst in 3 rd trimester and obese women exhibit a greater PSQI score than women with normal weight 21 . However, large scale prospective cohort studies are scarce.…”
Section: Introductionmentioning
confidence: 99%